EFFICACY OF OREGANO OIL, CITRUS OIL AND DIGESTAROM® P.E.P. ON NEWCASTLE DISEASE INFECTION IN BROILERS - Alazzawi, R. I.; Khammas, E. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present study was carried out to detect efficacy of essential oils (oregano oil, anise oil, citrus oil and Digestarom® P.E.P) as an antiviral on Newcastle disease infection in broilers.One hundred twenty, one-day-old broiler chickens (Copp500) were used. On day twenty, the one hundred chickens were divided into six groups.Each group contained 20 birds. All chicks were challenged with median) virus titer embryo infectious dose (EID50) 1ml per bird intraocular, intranasal and orally of the isolated very virulent Newcastle disease virus that identified by (HA, HI test, PCR and ICPI) and treated with the essential oils blend level used in drinking water for five days after challenge, G1 oregano oil1ml/L , G2 anise oil 1ml/L, G3 citrus oil1ml/L, G4 Digestarom® P.E.P 0.17ml/L, G5 control positive, and G6 control negative without any treatment. The chickens were observed for clinical signs, gross lesion and weight until the end of the experiment.The result indicated that G4showed high protect than other oils with percentage 95% of survival chicks and mean weight 2054.42 gm, then G1 90% survival chickens and mean weight 1971.17gm, G2 85% survival chicks and mean weight 2148.88gm,G3 75% survival chicks and mean weight 2227.07gm while G5 protection was 60% with mean weight 1866.67gm and G6showed 100% mortality rate.The results illustrate that G4 and G1 were the best treatments which recorded significantly ( P≤0.01) followed by G2 and G3 respectively which recorded significantly (P≤0.05) in comparison with G5and G6.